Effects of Dental Bleaching Treatment Ingredients and Their Influence on the Hardness of Tooth Enamel - Pindobilowo, Pindobilowo; Ariani, Dwi; M Asim, Fauziah (Formosa Journal of Applied Sciences, 2024)
Dental bleaching treatment is currently a trend at the moment. Dental bleaching treatment is not only for aesthetics but a person can become more confident with white teeth. However, it turns out that it has bad effects if it does not comply with correct dental principles, especially in selecting dental bleaching materials. Know the ingredients, effects and methods for whitening teeth, including those that can be used by patients themselves, with or without professional supervision, and products for professional use. This literature study uses the Narrative Review method. References were collected in the form of journals through databases and online websites of BMC Oral Health, PubMed, Wacana and Google Scholar. References are also selected through reference analysis in the form of research, articles and systematic reviews. Carbamide Peroxide can be recommended as a choice of dental bleaching agent because it has a remineralization effect and increases the microhardness of enamel after 8 weeks of application.